I met my younger selves for coffee an autofiction under a Deleuzian lens on understanding identity construction and authenticity as an influencer - Samonte, Bea A.
How often do you come across an influencer conducting academic research that bridges media studies and their lived experience in the influencer industry? While studies on influencer culture are growing, the voices of influencers themselves remain rare. In this qualitative study, I use autofiction to narrate a fictional conversation between my 2025 self and my past selves from 2021 to 2024. Grounded in Gilles Deleuze’s concepts of Virtuality and Actuality, the work views identity as a continuous process shaped by memory, media, and algorithmic culture. As “Beyapot,” I reflect on five years of being an influencer, where different virtuals of my identity emerged: the academic achiever, the lover girl, the beauty creator, the big sister, and the food vlogger. These are not contradictions, but expressions of different virtual selves shaped by desire, trends, and digital structures. What emerges is a rethinking of authenticity: not as fixed coherence, but as a moment-to-moment negotiation between who I was, who I am, and who I could become. Trends, platforms, and brand collaborations do not simply mirror identity—they help shape it. Ultimately, this thesis reframes influencer identity as an assemblage, a site of ongoing transformation within the flows of media life.